(untitled) (Gestão & Regionalidade, 2019)
South America is a major contributor to world agricultural production. The extensive growth of agricultural activity in the region is near to the limit, no option left to intensive growth, which is capable of producing economic development, to overcome challenges such as sustainability and competitiveness. Innovations are essential in this sense, especially those associated with precision agriculture (PA), taken as a set of organizational and process innovations that combine mechanization with information and communication technologies (ICT), allowing the singularization of the agricultural production unit by using spatial and temporal variability in small-scale areas. The goal of this work is to analyze the AP adoption "state of the art" in South America by collecting and analyzing the academic production on the subject. This exploratory research focuses on the experience of three countries representative of the economic and edaphoclimatic conditions of the Region: Argentina, Brazil and Colombia.